Evolution of grain trade patterns among RCEP member countries and the potential impacts of agreement signing - Minhao Lu; Yingmei Wu; Chao Zhang; Yang Wang; Jiahui Yang; Yi Huang; Yi Wang (Frontiers in Sustainable Food Systems)
IntroductionTrade plays a pivotal role in maintaining global grain security. However, the grain trade network (GTN) within Regional Comprehensive Economic Partnership (RCEP) member countries remains unclear. Analyzing grain flow characteristics and the agreement’s potential impacts are essential to fostering resilient economic and trade cooperation within the world’s largest free trade area.MethodsThis study constructed a trade network analysis framework incorporating complex network topology, competition intensity, interdependence intensity, and robustness. It examined the grain trade patterns and coopetition relationships from 2000 to 2020. Building on this, the study created the “Five Forces” model to analyze evolutionary mechanisms in the GTN and explored the potential impacts of trade agreements through trade diversion and creation effects.Results(1) The GTN has grown increasingly complex and interconnected, with key nodes exhibiting trends toward homogenization. By 2020, Australia, Viet Nam, Myanmar, Thailand, and Cambodia collectively accounted for 95.70% of total exports, emerging as major grain exporters in the GTN. (2) The GTN exhibits high competition and low interdependence. Populous countries with constrained arable land resources, such as China, Philippines, Malaysia, South Korea, and Indonesia, face intense import competition. Concerns over external supply security have led to diversified trade behaviors among member countries, fostering a trade pattern characterized by low interdependence (87.23%). (3) The robustness of the GTN has significantly improved due to the complexity of network structures and the homogenization of key node positions. Countries such as Thailand and Australia, with high Betweenness centrality values, play crucial roles in maintaining stability. Meanwhile, Viet Nam and China, as major import–export countries, are exerting growing influence in the GTN. (4) The evolution of the GTN is shaped by the interactive effects of five key forces: resource endowments, domestic demand, economic conditions, geopolitical relations, and important events. Differentiated tariff reduction commitments and reduced non-tariff measures are expected to generate trade diversion and creation effects. Such policy measures may reallocate intra-regional trade flows and expand trade volumes while intensifying import competition.DiscussionFrom a complex network perspective, this study provides valuable policy insights for RCEP member countries to leverage their strengths and participate more effectively in agricultural trade.